Book review: "Detention and torture in South Africa" - Harper, Ann (PINS-Psychology in Society, 2025)
Don Foster with Dennis Davis and Diane Sandler. (1987). Detention and Torture in South Africa; Psychological, legal and historical studies. Cape Town: David Philip. "Detention and Torture in South Africa" (1987) systematically documents and analyses the personal experiences and realities of those South Africans who have suffered physical and psychological trauma consequent on their treatment during detention under Security Legislation prior to the present State of Emergency.